PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONENNYA YANG TERCATAT PADA BURSA EFEK INDONESIA - Mukti Widodo (2022)
This study is a quantitative study that aims to determine the effect of liquidity, profitability, and leverage on stock prices. This study uses automotive companies and their components listed on the Indonesia Stock Exchange for the 2017-2020 period as the population. Sample selection is done by using saturated samples using all members of the population. Panel Data Regression Analysis was chosen as a hypothesis testing technique and supported by the use of the Eviews program and a significance level of 5% (0.05). Hypothesis testing obtained the following results; (1) there is a significant effect of liquidity on stock prices, (2) there is no significant effect of profitability on stock prices (3) there is a significant effect of leverage on stock prices.